Chirality-assisted synthesis of a very large octameric hydrogen-bonded capsule - Beaudoin, Daniel; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2016)
The strategy of chirality-assisted synthesis, which makes use of enantiomerically pure building blocks that are designed to associate in a single geometric orientation, was applied to synthesize an octameric hydrogen-bonded capsule with a cavity volume of 2300 Å3. This cube-shaped capsule forms even host-guest complexes with tetraalkylammonium ions, and accommodates the large tetrahexadecylammonium cation in its cavity. The use of an enantiopure building block was shown to be highly beneficial for capsule formation, whereas its racemate also generates a large amount of ill-defined aggregates in solution and crystallizes as a hydrogen-bonded network.
Gesehen am 04.05.2020